Psychological and Pedagogical Problems of Physical Education of Youth - Khabibova Gulya Gaybullaevna (Researchparks Publishing, 2022)
Physical education at all times has been an indicator of endurance, the importance of physical activity in the life of a person. Physical culture made it possible to improve such factors as: endurance, determination, self-control, patience, leadership skills. In the modern world, society also seeks to comprehend and more deeply develop the psychological aspects of physical culture. Young people today actively spend their free time in gyms, outdoors or in sports clubs. In this regard, the formation, formation and self-improvement of physical activity takes place, as well as the process of pedagogical education and personality formation.